Flash Bottom‐Up Arc Synthesis of Nanocarbons as a Universal Route for Fabricating Single‐Atom Electrocatalysts. Issue 8 (18th June 2021) - Jung, Jae Young; Jang, Jue‐Hyuk; Kim, Jeong‐Gil; Lee, Kug‐Seung; Lim, Hyung‐Kyu; Kim, Pil; Chang, Robert P. H.; Park, Ji‐Woong; Yoo, Sung Jong; Kim, Nam Dong
Abstract: Despite considerable development in the field of single‐atom catalysts (SACs) on carbon‐based materials, the reported strategies for synthesizing SACs generally rely on top‐down approaches, which hinder achieving both simple and universal synthesis routes that are simultaneously applicable to various metals and nanocarbons. Here, a universal strategy for fabricating nanocarbon based‐SACs using a flash bottom‐up arc discharge method to mitigate these issues is reported. The ionization of elements and their recombination process during arc discharge allows the simultaneous incorporation of single metal atoms (Mn, Fe, Co, Ni, and Pt) into the crystalline carbon lattice during the formation of carbon nanohorns (CNHs) and N‐doped arc graphene. The coordination environment around the Co atoms of Co1 /CNH can be modulated by a mild post‐treatment with NH3 . As a result, Co1 /CNH exhibits good oxygen reduction reaction activity, showing a 1.92 times higher kinetic current density value than the commercial Pt/C catalyst in alkaline media. In a single cell experiment, Co1 /CNH exhibits the highest maximum power density of 472 mW cm −2 compared to previously reported nonprecious metal‐based SACs. Abstract : The authors report a universal strategy for fabricating single‐atom catalysts (SACs) using a flash bottom‐up arc discharge. It allows the simultaneous incorporation of metal atoms into the carbon lattice during the formation of nanocarbons. It is applicable to various metals and nanocarbons. In a single cell experiment, Co1 /CNH catalysts exhibit the highest maximum power density compared to reported nonprecious metal‐based SACs.